Efforts to Improve the Ability of Mathematical Problem Solving in the Form of Story Questions Through the Polya Method for Class III Students of SDN Karanglo Cilongok - Siti Lestari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This article is intended to describe the Efforts to Improve the Ability of Mathematical Problem Solving Ability in the Form of Story Questions through the Polya Method in Class III Students of SDN Karanglo Cilongok.The research was conducted in class III SD Negeri Karanglo, in three cycles. Each cycle of research activities includes planning, action, observation and reflection. The research subjects were 19 students, the data collection method used was observation and test.The results of this study were that by using Polya's steps, the students 'ability to solve story problems could be improved, the increase in the ability of students in cycle I by an average of 6.7 became an increase to 8.6 at the end of cycle 2. Students' abilities in using the steps His polya steps to solve mathematical problem solving in the form of story problems in cycle I are 40%, in cycle II are 80%, and in cycle 3 are 90%. The absorption power of students at the end of cycle III who scored 9.2 and above was 92% said to be complete learning.The conclusion of this research is that by using the Polya method, student achievement can be improved.